A Consumption and Investment Problem via a Markov Decision Processes Approach with Random Horizon. (7th June 2022) - Paredes Pérez, Octavio; Vázquez Guevara, Víctor Hugo; Cruz-Suárez, Hugo
Abstract : This work is devoted to a consumption and investment problem, in which there is an investor with certain initial wealth with the possibility of deciding how much of such wealth will be consumed and how much will be invested in each of a series of successive times. The key issue is to find a wealth assignation rule in order to maximize the performance criteria; such dilemma will be achieved by the dynamic programming technique for the Markov decision processes with random horizon.